2004
DOI: 10.1515/jpem.2004.17.6.853
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Hyperlipidemia after a Fat Loading Test in Minority Adolescents with Type 2 Diabetes Mellitus and Obesity

Abstract: The continuing increase in the incidence of type 2 diabetes mellitus (DM2) and obesity in children and adolescents is attributable to excessive caloric intake. Abnormal lipid metabolism in the postprandial state leads to long exposure of the vasculature to hyperlipidemia. Most children and adolescents with DM2 are obese, and many have fasting hypertriglyceridemia. Clustering of hyperlipidemia, DM2 and obesity increases the risk for cardiovascular disease. We therefore studied lipids, insulin, C-peptide, and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
20
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 11 publications
5
20
0
2
Order By: Relevance
“…The increased triglyceride levels during the fat-loading tests observed in our study are consistent with findings reported by others (37)(38)(39) and have been discussed previously (40). The relationship between elevated PAI-1, insulin resistance, and hypertriglyceridemia is established (2,6,17,18,36,41) and is shown in our study.…”
Section: Discussionsupporting
confidence: 93%
“…The increased triglyceride levels during the fat-loading tests observed in our study are consistent with findings reported by others (37)(38)(39) and have been discussed previously (40). The relationship between elevated PAI-1, insulin resistance, and hypertriglyceridemia is established (2,6,17,18,36,41) and is shown in our study.…”
Section: Discussionsupporting
confidence: 93%
“…These estimates are broadly consistent with previous cross-sectional studies that have found significant differences in PPL when assigning 8-15 subjects per group (Gill et al 2004;Umpaichitra et al 2004). Nevertheless, we acknowledge that it is possible that a larger absolute difference in body composition, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…However, TG levels returned to baseline values at 6 h in the NW group but were still elevated at 6 h in the OW group, suggesting a delayed clearance. Coupled with the correlations of sum of skinfolds with TG AUC, and previous evidence showing greater postprandial TG responses to a high-fat meal in obese adolescents and adults (Gill et al 2004;Moreno et al 2001;Umpaichitra et al 2004), there remains the possibility that OW adolescents are at greater risk of postprandial exposure to atherogenic particles. The mechanisms responsible for the exercise-induced reduction in PPL in the present study have not been fully characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The several OTTT protocols that have been investigated include those that vary fat intake according to body weight (1 g dairy cream/kg body weight) as well as those that use a fixed combined challenge (50 g fat plus 50 g carbohydrate) (14 ). In controlled studies of healthy individuals, as well as those with metabolic syndrome or diabetes, methods that measure blood concentrations 2-4 h after the administration of calibrated fat loads have proved to be reproducible and palatable approaches for assessing postchallenge triglyceride concentrations (14,15 ).…”
mentioning
confidence: 99%